Assessing Public Financing for Nutrition in Sri Lanka (2014–2018) - World Bank (Washington, DC: World Bank, 2020)
This study aims to assess the public financing for nutrition in Sri Lanka. The primary purpose is to understand the size and share of public investments in nutrition relative to the overall level of public expenditure in the country. Second, it discusses whether the nutrition interventions in which the government budget is spent are in line with the global evidence base and priorities set out in national policies. It also provides some recommendations on how such assessments could be improved from challenges and difficulties faced in undertaking this exercise. This report begins with background and contextual information of nutrition in Sri Lanka (chapter two). It then provides an overview of globally practiced nutrition interventions and policies and programs that have been implemented in the country (chapter three). Chapter four describes the approach used for the analysis followed by results and findings in chapter five. The report concludes with brief discussions on key findings, challenges, and recommendations in chapter six.